Data Visualization Design of Real-Time Power Grid Operation State Monitor - Siqi He; Chunyu Deng; Yupeng Shao; Yueyue Wang (Dianxin kexue)
The electricity load data of the urban distribution network from Zhejiang province was chosen as work case. By conducting data visualization design from the prospects of designing psychology and interaction design and sending graphical signal to staff，a solution of monitoring the operation state of power was explored. The solution has the effect of relating the date，depriving information，reducing work complicity and increasing the work efficiency. Furthermore，it is a solution with expansibility and universality.